Shaggy-like Ru-clusters decorated core-shell metal-organic framework-derived CoOx@NPC as high-efficiency catalyst for NaBH4 hydrolysis. (11th February 2021) - Dou, Shasha; Zhang, Wanyu; Yang, Yuting; Zhou, Shuqing; Rao, Xianfa; Yan, Puxuan; Isimjan, Tayirjan Taylor; Yang, Xiulin
Abstract: Achieving high catalytic performance with the lowest possible amount of noble metal is critical for any catalytic applications. Herein, we report a controllable method of preparing low Ru loaded, N-doped porous carbon embedded with cobalt oxide species (Ru/CoOx @NPC) using core-shell metal-organic framework (MOF) as a template. The optimized catalyst exhibits a highly powerful yet stable performance of H2 production through sodium borohydride (NaBH4 ) hydrolysis. The Ru/CoOx @NPC catalyst shows a fast H2 generation rate (8019.5 mL min −1 gcat −1 ), high turnover frequency (1118.6 mol min −1 molRu −1 ), and reusability. The carbonized ZIF-8 core and the ZIF-67 outer shell supplies a porous carbon moiety that not only improves the conductivity and but also provides uniform distribution of the active sites. The XPS analysis indicates that there is a strong electronic interaction between Co species and Ru species. The superior catalytic performance can be attributable to the large specific surface area as well as the synergy between Co-oxide and Ru clusters. Graphical abstract: Shaggy-like Ru-clusters decorated core-shell MOF-derived N-doped porous carbon embedded with cobalt oxide species is fabricated by a seed-mediated growth technique plus precise calcination. The optimized catalyst exhibits a highly powerful yet stable reusability performance of H2 production through NaBH4 hydrolysis. Image 1 Highlights: Ru/CoOx @NPC is fabricated by a seed-mediated growth plus precise calcination. The catalyst exhibits high activity and reusability for NaBH4 hydrolysis. Carbonized ZIF-8 and ZIF-67 provide high conductivity and rich active sites. The superior performance attributed to the synergy of Co oxides and Ru clusters.